A cross-country study of union membership - Blanchflower, David G. (Bonn, 2006)
"This paper examines changes in unionization that have occurred over the last decade or so using individual level micro data on twenty seven of the thirty OECD countries, with particular emphasis on Canada, the United Kingdom and the United States. Micro-data is also used to model union membership in a further eleven non-OECD countries. Union density is found to be negatively correlated with level of education in the private sector and positively correlated in the public sector. The probability of being a union member is found to follow an inverted U-shaped pattern in age, maximizing in Canada, the USA and the UK in the mid to late 40s. This inverted U-shaped pattern is repeated in a further thirty countries (Australia; Austria; Bangladesh; Belgium; Bulgaria; Chile; Czech Republic; Denmark; Germany; Estonia; Finland; France; Greece; Hungary; Ireland; Israel; Japan; Luxembourg; Mexico; Netherlands; New Zealand; Norway; Poland; Portugal; Russia; Slovak Republic; Slovenia; Spain; Sweden and Switzerland). I consider the question of why this inverted U-shape in age exists across countries with diverse industrial relations systems including early retirement and cohort effects."